PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL AZANA BOUTIQUE BANDAR LAMPUNG - Pratama, Deska Hasan; Chandra, Ade; Ahadi, Hamartoni (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of the work environment and job satisfaction on employee performance at Azana Boutique Hotel Bandar Lampung. Using a quantitative associative approach with a saturated sample of 74 employees, data were analyzed via multiple linear regression. Results show that both the work environment and job satisfaction significantly and positively affect performance, individually and jointly, explaining 77.6% of the variance. Conducted amid organizational uncertainty, the study underscores the importance of a conducive environment and job satisfaction in sustaining employee performance in the hospitality sector.